2013
DOI: 10.1111/jnu.12051
|View full text |Cite
|
Sign up to set email alerts
|

A New Theoretical Model for the Development of Pressure Ulcers and Other Dependence‐Related Lesions

Abstract: The prevention and treatment of these lesions requires a correct diagnosis and differentiation of their cause and management of the risk dimensions involved. The type of lesion also influences the selection of local approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
20

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 29 publications
0
37
0
20
Order By: Relevance
“…During movement to the examination table or bed, a patient can experience friction and shear, important factors in the development of pressure ulcers. 18,30,31 Use of vasopressors and low systolic blood pressure were significant variables in our study.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…During movement to the examination table or bed, a patient can experience friction and shear, important factors in the development of pressure ulcers. 18,30,31 Use of vasopressors and low systolic blood pressure were significant variables in our study.…”
Section: Discussionmentioning
confidence: 82%
“…However, an interaction between multiple variables most likely explains why a pressure ulcer develops in some patients but not in other patients at risk. 1,18,20 The variables we examined were significantly associated with the development of pressure ulcers, and 4 variables were significant predictors in both regression models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Other organizations have adopted similar definitions but with some modifications. Thanks to the new model created by García-Fernández et al, 11 a PU is considered as a dependence-related injury. Thus, the National Group for the Study and Assessment of Pressure Ulcers (GNEAUPP) 10,12 suggested in 2014 the following definition: "A pressure ulcer is a localized lesion on the skin and/or the underlying tissue, over a bony prominence, as a result of pressure, or pressure in combination with shear forces.…”
Section: Neonatal Pusmentioning
confidence: 99%